2021
DOI: 10.21037/atm-21-3090
|View full text |Cite
|
Sign up to set email alerts
|

Comparative healing of swine skin following incisions with different surgical devices

Abstract: Background: Electrosurgical technology is widely used in surgical dissection and hemostasis, but the generated heat creates thermal injury to adjacent tissues and delays wound healing. The plasma blade (PB) applies pulsed radiofrequency (RF) to generate electrical plasma along the edge of a thin, flat, insulated electrode, minimizing collateral tissue damage. This study aimed to evaluate wound healing in swine skin following incision with a new surgical system that applies low-temperature plasma (NTS-100), a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The PB is reported to perform better than the ES in terms of wound healing and duration time for procedures such as tonsillectomy, breast reconstruction, the replacement of implanted medical devices, and surgical debridement of chronic ulcers (4,22,23). Previous research has also confirmed that the NTS-100 is superior to the most developed PB in terms of the number of tissue injuries and its cutting and coagulating capability (24), and the NTS-100 has already been used effectively in breast, head and neck, and general surgery. Our findings illustrate that the NTS-100 generated substantially less hazardous surgical smoke than did the PB or the ES.…”
Section: Discussionmentioning
confidence: 99%
“…The PB is reported to perform better than the ES in terms of wound healing and duration time for procedures such as tonsillectomy, breast reconstruction, the replacement of implanted medical devices, and surgical debridement of chronic ulcers (4,22,23). Previous research has also confirmed that the NTS-100 is superior to the most developed PB in terms of the number of tissue injuries and its cutting and coagulating capability (24), and the NTS-100 has already been used effectively in breast, head and neck, and general surgery. Our findings illustrate that the NTS-100 generated substantially less hazardous surgical smoke than did the PB or the ES.…”
Section: Discussionmentioning
confidence: 99%